2000
DOI: 10.1063/1.1150456
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Hadamard transform time-of-flight mass spectrometer

Abstract: A pseudorandom time-of-flight method ͑also called the cross-correlation method͒ has been used to perform time-of-flight mass spectrometry with a duty cycle of 50%. Modulation of an ion beam is accomplished by deflecting the ion beam with an interleaved comb of oppositely charged elements. Maximum-length pseudorandom sequences based on Hadamard-type difference sets are produced by feedback shift register circuitry and used for ion beam modulation. The inverse transformation of the recorded signal is carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
39
0
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 29 publications
0
39
0
1
Order By: Relevance
“…Thus, there is a mass cutoff, above which the modulation efficiency is significantly reduced. This mass cutoff has been reported previously [14], and sets an upper limit on the mass that can be analyzed using HT-TOFMS. The mass cutoff M cutoff is given by the expression [15] …”
Section: Understanding and Optimizing 2c-ht-tofmsmentioning
confidence: 70%
See 1 more Smart Citation
“…Thus, there is a mass cutoff, above which the modulation efficiency is significantly reduced. This mass cutoff has been reported previously [14], and sets an upper limit on the mass that can be analyzed using HT-TOFMS. The mass cutoff M cutoff is given by the expression [15] …”
Section: Understanding and Optimizing 2c-ht-tofmsmentioning
confidence: 70%
“…This sweeping appears as two separated peaks in I(t). When combined with data acquisition oversampling, this mode of operation, known as differential impulse sweep mode, can be used to increase the mass resolution by sacrificing sensitivity [14]. Thus, in normal mode of operation, V p must be above a threshold voltage, but too much voltage causes reduction in the modulation efficiency for the outer channel.…”
Section: Understanding and Optimizing 2c-ht-tofmsmentioning
confidence: 99%
“…Some other methods include weaving against the threads on nylon bolts [22], etching a thin metal foil [23], and wire-bonding to metal deposited on ceramic frame [24]. Brock et al [14,25] reported a BNG wire spacing of 0.16 mm in 1998 achieved by manually weaving wires onto an etched silicon frame under a microscope. This work represents a significant improvement in reducing the wire spacing, but the procedure is extremely laborious, requiring several days to complete the assembly [26].…”
mentioning
confidence: 99%
“…Use of these matrices in the deconvolution step led to marked improvements in spectral resolution but require full knowledge of the encoding defects. O ver the past few years, our group has published a series of articles describing Hadamard transform time-of-flight mass spectrometry (HT-TOFMS) [1][2][3][4][5]. Other groups have described the application of Hadamard multiplexing to absorption spectroscopy [6], Raman spectrometry [7], photoacoustic depth profiling [8], and capillary electrophoresis [9 -11].…”
mentioning
confidence: 99%
“…Detailed descriptions of how encoding sequences are applied in HT-TOFMS have been presented previously [2], and only a brief review is given here. Ions are accelerated toward a BNG.…”
mentioning
confidence: 99%